Research on simulation and modeling of simple and cost-effective BLDC motor drives. (2nd January 2017) - Shokri, Gh.; Naderi, E.
Abstract: Brushless DC (BLDC) motors have been increasingly considered in variable speed drives in wide array of applications due to their significant features such as high efficiency, power density, and torque density. Cost minimization of variable speed drives is accomplished by topological and control approaches. Minimum number of switches and current sensors, and eliminating the position sensors are desired in the topological approach. Moreover, the control algorithms must be simple, effective, and adjustable with drive topology to produce the desired speed-torque characteristics. In this paper, a review of four different drives of BLDC motor is presented, with emphasis on control strategies, drive topologies, and analysis of simulation results. In addition, speed control of these drives using Particle Swarm Optimization based on tuned Proportional Integral controller is regulated because classic control theory is complex and requires the precise recognition of system to develop a desired controller. Finally by considering the torque ripple, a general comparison between different methods with various strategies has been made.